1, 2‐Addition of Alkyl Grignard Reagents to the Nitro Group: Simple Access to 2‐[Alkyl(hydroxy)amino]pyridine N‐Oxides and 2‐Alkylaminopyridine N‐Oxides. Issue 27 (30th July 2013) - Liu, Kun‐Ming; Zhang, Fang; Duan, Xin‐Fang
Abstract: The unexpected 1, 2‐addition of various alkyl Grignard reagents to nitro groups is described. A simple treatment of a 2‐nitropyridine N ‐oxide with an alkyl Grignard reagent results in a 2‐[alkyl(hydroxy)amino]pyridine N ‐oxide as the result of a 1, 2‐addition to the nitro group. Moreover, 2‐(alkylamino)pyridine N ‐oxides can also be obtained from this 1, 2‐addition after a reductive workup by using NaBH4 /FeCl3 . This work shows another facet of the reactions between alkyl Grignard reagents and nitro groups, and provides a simple method for the formation of carbon–nitrogen bonds without a transition metal catalyst. Abstract : The unexpected 1, 2‐addition of alkyl Grignard reagents to nitro groups is described. 2‐[Alkyl(hydroxy)amino]pyridine N ‐oxides and 2‐(alkylamino)pyridine N ‐oxides can be prepared by 1, 2‐addition of alkyl Grignard reagents to the nitro group of 2‐nitropyridine N ‐oxides. This new reaction between alkyl Grignard reagents and nitro groups provides a simple method for carbon–nitrogen bond formation.